THE ECONOMIC IMPACT ON GLOBAL TOURISM - Sofronov, Bogdan (Annals of Spiru Haret University. Economic Series, 2017)
Tourism is an important economic activity in most countries around the world. As well as its direct economic impact,the industry has significant indirect and induced impacts. The outlook for the Tourism sector in 2017 remains robust and will continue to be at the forefront of wealth and employment creation in the global economy, despite the emergence of a number of challenging headwinds. In tourism, GDP growth is expected to accelerate to 3.8%, up from 3.1% in 2016. As nations seem to be looking increasingly inward, putting in place barriers to trade and movement of people, the role of Tourism becomes even more significant, as an engine of economic development and as a vehicle for sharing cultures, creating peace, and building mutual understanding.